2006
DOI: 10.1097/01.hco.0000231410.07426.9b
|View full text |Cite
|
Sign up to set email alerts
|

An evidence-based approach to the management of pulmonary arterial hypertension

Abstract: The diagnostic criteria for pulmonary arterial hypertension should be revised to include PVR. Sildenafil's efficacy and price recommend it as a first-line oral therapy. New pulmonary arterial hypertension-regression therapies and therapeutic combinations offer the potential for cure of pulmonary arterial hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 62 publications
(59 reference statements)
0
38
1
Order By: Relevance
“…Trigger of EC proliferation and plexiform lesion formation by proliferating ECs are important pathological changes in PAH ( 18 ). However, whether EETs are responsible for the tumorlets of endothelial cells that obliterate pulmonary arteries, as well as the relative mechanisms, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Trigger of EC proliferation and plexiform lesion formation by proliferating ECs are important pathological changes in PAH ( 18 ). However, whether EETs are responsible for the tumorlets of endothelial cells that obliterate pulmonary arteries, as well as the relative mechanisms, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In a double-blind randomized trial, Wilkins et al 35 showed that sildenafil (but not bosentan, an endothelin receptor antagonist also approved for the treatment of PAH) decreased RVH (studied by magnetic resonance imaging), although the relative importance of decreasing afterload versus direct antihypertrophic effects on the RV is difficult to determine in vivo. Because of its effectiveness, excellent toxicity profile, and relatively low price compared with the other available therapies, 36 sildenafil use is rapidly increasing in PAH patients, and its potential benefit in a number of cardiovascular disorders is being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…10 Oral therapies for PAH such as endothelin receptor antagonists (eg, bosentan) and phosphodiesterase inhibitors (eg, sildenafil) may improve symptoms and the quality of life of PAH patients, but it remains to be determined whether they improve survival. The overall improvement in hemodynamics is minimal, and the functional capacity improvement with these therapies is similar to improvements achieved by exercise training alone.…”
mentioning
confidence: 99%
“…The overall improvement in hemodynamics is minimal, and the functional capacity improvement with these therapies is similar to improvements achieved by exercise training alone. 10,11 The ease of delivery of these therapies contributes to their heavy use. The emerging idea that the next breakthrough in management of PAH may be a combination of existing therapies is of concern if this in any way impedes the development of new testable ideas.…”
mentioning
confidence: 99%
See 1 more Smart Citation